RANCANG BANGUN OPTIMALISASI PANEL SURYA DUAL AXIS DENGAN MENGGUNAKAN SENSOR INTENSITAS CAHAYA - Sulistyowati, Riny; Sujono, Hari Agus; Munir, Misbahul (Jurnal Media Elektro, 2024)
The results from the solar power generation system depend on the input and duration of eh sunlight entering the solar panel. However, problems will come when the sun changes every day from east to west and the weather changes frequently. They will result in the power generated by static solar panels not being optimal. This research collected data in East Kalisari Village, Surabaya, because this location has good potential for solar energy according to BMKG data from November 2022, which was the peak of the rainy season. The data showed the average solar radiation from 06.00 to 18.00 for 6 hours. For this reason, the researcher designed a dynamic solar panel that could follow the movement of the sun. A solar power plant optimization system is needed to maximize the acquisition of solar energy and increase the power generated by solar panels. The design of optimizing dual-axis solar panels using light intensity sensors could solve some problems of static solar panels, which could not follow the movement of sunlight. As a result, the power generated by solar panels could be optimized, and the potential of solar energy in East Kalisari Village, Surabaya, could be optimally used.